2017
DOI: 10.18632/oncotarget.16992
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen promotes tumor metastasis via estrogen receptor beta-mediated regulation of matrix-metalloproteinase-2 in non-small cell lung cancer

Abstract: In non–small cell lung cancer (NSCLC), estrogen significantly promotes NSCLC cell growth via estrogen receptor beta (ERβ). However, the effects by which ERβ contributes to metastasis in NSCLC have not been previously reported. This study aims at defining whether the stimulation of ERβ promotes NSCLC metastasis in vitro and in vivo. Here, Our results showed that estrogen and ERβ agonist enhanced aggressiveness of two lung cancer cell lines (A549 and H1793) and promoted murine lung metastasis formation. ER-inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 42 publications
6
61
0
Order By: Relevance
“…Numerous evidences have shown that MMPs have been shown to involve metastasis process including cell adhesion, migration and invasion . MMPs have been shown to be present in melanoma and the inhibition of MMPs which associated with suppressed cancer cell metastasis such as inhibited MMP‐2 could suppressed tumor metastasis . MMP‐9 is closely correlated with tumor metastasis in various cancers and it has been reported that MMP‐9 and other MMPs may be considered as effective targets for anti‐cancer drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidences have shown that MMPs have been shown to involve metastasis process including cell adhesion, migration and invasion . MMPs have been shown to be present in melanoma and the inhibition of MMPs which associated with suppressed cancer cell metastasis such as inhibited MMP‐2 could suppressed tumor metastasis . MMP‐9 is closely correlated with tumor metastasis in various cancers and it has been reported that MMP‐9 and other MMPs may be considered as effective targets for anti‐cancer drugs .…”
Section: Discussionmentioning
confidence: 99%
“…However, BITC inhibited MMP-2 activity but increased MMP-2 protein levels at all examined doses following 24 or 48 h treatment. It has been reported that MMP-2 is associated with tumor invasion and angiogenesis and that inhibited MMP-2 could suppress tumor metastasis (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The results further indicated that treatment with estrogen or ERβ activation also significantly promotes lung cancer cell metastasis by upregulating invasiveness-associated matrix metalloprotease 2 (MMP2) both in vitro and in vivo [13]. Therefore, to markedly depress NSCLC metastasis and to finally detect a new treatment strategy for advanced lung cancer patients, inhibiting the effect induced by estrogen on NSCLC cells is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Data from urethane-induced primary NSCLC mouse models indicate that the inhibition of ERβ by fulvestrant can significantly reduce lung cancer formation and pleural metastasis [14]. In NSCLC cell lines, proliferation-associated IGF-1 and invasion-associated MMP2 expression levels are downregulated in response to antiestrogens in vitro [13,15]. A clinical study including 26 women with second primary lung cancer among 6,361 diagnosed breast cancer patients provided evidence of a longer cancerspecific survival rate in the patients treated with antiestrogens for breast cancer compared with those treated without antiestrogens [16].…”
Section: Introductionmentioning
confidence: 99%